The customary method of finding the inverse is some variant of the method. Whatever method you will use, make sure you do the exact same steps in the exact same order every time, so you remember those steps when you get to the test.
Find the inverse of y = 3x – 2.
Here's how the process works:
Here's original function:
Now try to solve for "x =":
y+2 = 3x
y+2 / 3 =x
Once I have "x =", I'll switch x and y; the "y =" is the inverse.
y=x+2 / 3
Then the inverse is y = (x + 2) / 3
Sep 27th, 2014
Are you studying on the go? Check out our FREE app and post questions on the fly!